2012
DOI: 10.1063/1.4754151
|View full text |Cite
|
Sign up to set email alerts
|

Reconnection events in two-dimensional Hall magnetohydrodynamic turbulence

Abstract: The statistical study of magnetic reconnection events in two-dimensional turbulence has been performed by comparing numerical simulations of magnetohydrodynamics (MHD) and Hall magnetohydrodynamics (HMHD). The analysis reveals that the Hall term plays an important role in turbulence, in which magnetic islands simultaneously reconnect in a complex way. In particular, an increase of the Hall parameter, the ratio of ion skin depth to system size, broadens the distribution of reconnection rates relative to the MHD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 34 publications
3
39
0
Order By: Relevance
“…It is found that at small to moderate wave numbers, which can extend to scales below the ion inertial length, E M (k)/E V (k) is in near equipartition. Unlike MHD, at large wave numbers the ratio becomes magnetically dominated and scales as ǫ Current structures in HMHD are found to be narrower and more intense than in MHD, as has been noted by various other authors [46,49,51]. In particular, it is found that while current and vorticity structures have nearly equal sizes on average in MHD, in HMHD current structures become narrower and vorticity structures become broader.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…It is found that at small to moderate wave numbers, which can extend to scales below the ion inertial length, E M (k)/E V (k) is in near equipartition. Unlike MHD, at large wave numbers the ratio becomes magnetically dominated and scales as ǫ Current structures in HMHD are found to be narrower and more intense than in MHD, as has been noted by various other authors [46,49,51]. In particular, it is found that while current and vorticity structures have nearly equal sizes on average in MHD, in HMHD current structures become narrower and vorticity structures become broader.…”
Section: Discussionsupporting
confidence: 55%
“…Two dimensional (2D) simulations have found reconnection sites in the turbulence become similar in structure to laminar studies of HMHD reconnection which exhibit bifurcated current sheets and quadrupolar magnetic fields [51]. Dmitruk and Matthaeus [52] found that while the magnetic field was largely unchanged by the addition of the Hall effect, the electric field was more intermittent.…”
Section: Introductionmentioning
confidence: 99%
“…A value of the connectivity index d > 0 (d = 0for a compact non-fractal set) indicates that there are topological obstacles for the current flow, so that a highly structured irregular pattern for the current is formed. These obstacles can be associated with the formation of coherent magnetic structures as observed in numerical simulations (Wu & Chang 2000;Servidio et al 2011;Donato et al 2012). We underline that the above scenario is in agreement with a coarse-grained nature of plasma media due to the formation of multiscale coherent structure as suggested by Chang (1999).…”
Section: Discussionsupporting
confidence: 71%
“…We underline that the above scenario is in agreement with a coarse-grained nature of plasma media due to the formation of multiscale coherent structure as suggested by Chang (1999). Furthermore, the above considerations support the view of a not space-filling nature of the reconnection region, which can also be relevant to overcome the inherent difficulties of the Sweet-Parker model as described in Materassi & Consolini (2007) and Donato et al (2012).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation